Development of Android-Based Mobile Learning Media on Cell Material to Improve Students’ Learning Outcomes - Mohammad Fatkhul Amien; Saptono, Sigit (Journal of Biology Education, 2025)
The widespread use of Android-based devices enables the application of mobile learning as a flexible and effective learning method. The development of the Society 5.0 concept emphasizes that humans are the center of innovation in utilizing technological advances born from the Industrial Revolution 4.0 era. The purpose of this study is to develop Android-based learning media on the structure and function of cell organelles, analyze the effectiveness of the media in improving students' cognitive learning outcomes, and determine the responses of teachers and students to the application of Android-based mobile learning media on the structure and function of cell organelles. The research method Research and Development (R&D) with a modified 4-D model design (Define, Design, Development, and Disseminate). This study involved 42 students from grade XI and biology teachers. The analysis was carried out based on validation tests by experts, analysis of student and teacher questionnaire responses, and analysis of cognitive learning outcomes with N-gain. Teacher and student responses were very good to the use of learning media Structure and Function of Cell Organelles with a value of 96% and 92%. The N-gain analysis for improving cognitive learning outcomes was found to be effective with a value of 0.78 and an effectiveness of 77.95%. The development of this Android-based learning media on the Structure and Function of Cell Organelles received a very positive response from teachers and students, and was found to be feasible and effective in improving students' cognitive learning outcomes.